Convenient massage type graduated decompression stretch sock wearing assisting device - YU DAGANG; LU WEI; YE SUFANG; ZHENG ZHENZHEN; LI XIAOYANG; ZHANG XINMEI (2021)
The invention discloses a convenient massage type graduated decompression stretch sock wearing assisting device, which comprises an arc-shaped semi-groove boot leg, an arc-shaped opening of the arc-shaped semi-groove boot leg is connected with a telescopic groove piece capable of being folded in the arc-shaped semi-groove boot leg, four pneumatic massagers are arranged on the inner side of the arc-shaped semi-groove boot leg, a power source, a massager power switch and a massager gear adjusting key are arranged on the outer side face of the arc-shaped semi-groove boot leg; the power source, the pneumatic massager, the massager power switch and the massager gear adjusting key are electrically connected in sequence, two lifting ropes are connected to the end, close to the arc-shaped opening, of the arc-shaped semi-groove boot leg, and the arc-shaped semi-groove boot leg is connected with an adhesive bandage. The stretch sock provided by the invention has the advantages that the comfort of a patient and the wear